Naval Strategy in the Normandy Invasion - Nazirah, Nazirah; Seomantri, Asep Iwa (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The Normandy invasion, also known as Operation Overlord, was one of the most monumental events in the history of World War II. On June 6, 1944, nearly three million Allied troops crossed the English Channel from England into France occupied by Nazi Germany. The invasion of Normandy opened the way to the liberation of Europe and finally ended World War II. Naval strategy was crucial in this operation to support the landing of troops on the beaches of Normandy. In the context of naval strategy, the Normandy invasion involved coordination between the navy, army, and air force. The writing methodology uses a descriptive method by analyzing the facts that occurred during the 1944 Normandy battle and is supported by literature studies, literature and various scientific journals.